2014
DOI: 10.1063/1.4866799
|View full text |Cite
|
Sign up to set email alerts
|

Phonons with long mean free paths in a-Si and a-Ge

Abstract: We investigated phonons with long mean free paths (MFPs) in amorphous Si (a-Si) and amorphous Ge (a-Ge). The thermal conductivity of a-Si and a-Ge thin films prepared by magnetron sputtering was found to depend on film thickness and deposition temperature. From the film thickness dependence, we conclude that phonons with MFPs longer than 100 nm contribute to heat transport in a-Si and a-Ge. Also, as deposition temperature was increased, phonons with MFPs ranging from 100 to 250 nm in a-Si and from 15 to 250 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 21 publications
3
25
0
Order By: Relevance
“…The recent paper reported that the κ value depended on the formation temperature and thickness [29]. The κ value of amorphous Si formed under similar formation temperature and thickness of our CSN film is 0.98-0.99 W m À 1 K À 1 [29]. The consistency of the κ values reported from several groups [26][27][28][29] exhibited the high reliability of its value.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The recent paper reported that the κ value depended on the formation temperature and thickness [29]. The κ value of amorphous Si formed under similar formation temperature and thickness of our CSN film is 0.98-0.99 W m À 1 K À 1 [29]. The consistency of the κ values reported from several groups [26][27][28][29] exhibited the high reliability of its value.…”
Section: Resultssupporting
confidence: 69%
“…The κ value of amorphous Si formed under similar formation temperature and thickness of our CSN film is 0.98-0.99 W m À 1 K À 1 [29]. The consistency of the κ values reported from several groups [26][27][28][29] exhibited the high reliability of its value. In order to investigate whether this anomalous reduction comes from unique properties of CSNs or from conventional interfacial thermal resistance and classical size (ballistic) effect [30] of Si thermal conductivity, we calculated κ for a superlattice (SL) of amorphous SiO 2 ($0.3 nm)/Si (thickness of t Si ) under two different scenarios: fully diffusive (open triangles) and quasi-ballistic Boltzmann phonon transport (close triangles), by using the finite element and Monte Carlo methods [31], respectively as shown in Figure 3b.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Although thermal energy in the amorphous materials is mainly transported by non-propagating diffusons 37 , it is known that there are also low frequency propagons 32 with mean free path exceeding tens of nanometers [38][39][40][41][42] . Such low frequency propagation is absent in SiNC because mean free paths of acoustic phonons are ultimately reduced as described above.…”
mentioning
confidence: 99%
“…This result is similar to the results for a-Si and a-Ge from previous reports. [23][24][25][26][27][28][29] Previous work shows that the thermal conductivity of a-Si lms with thicknesses less than 100 nm do not show observable lm size dependence. 24 If we assume this remains true for our Al-doped a-Si lms, by tting the two data points (50 and 100 nm, 50 and 150 nm) for each Al doping concentration, we can calculate the thermal conductivities of the 100 and 150 nm-thick lms.…”
Section: Methodsmentioning
confidence: 99%